Pro-inflammatory T-Lymphocytes rapidly infiltrate into the brain and contribute to neuronal injury following cardiac arrest and cardiopulmonary resuscitation - Deng, Guiying (2014)
Although inflammatory mechanisms have been linked to neuronal injury following global cerebral ischemia, the presence of infiltrating peripheral immune cells remains understudied. We performed flow cytometry of single cell suspensions obtained from the brains of mice at varying time points after global cerebral ischemia induced by cardiac arrest and cardiopulmonary resuscitation (CA/CPR) to characterize the influx in lymphocytes into the injured brain. We observed that CA/CPR caused a large influx of lymphocytes within 3 hours of resuscitation that was maintained for the 3 day duration of our experiments. Using cell staining flow cytometry we observed that the large majority of infiltrating lymphocytes were CD4(+) T cells. Intracellular stains revealed a large proportion of pro-inflammatory T cells expressing either TNFα or INFγ. Importantly, the lack of functional T cells in TCRα knockout mice reduced neuronal injury following CA/CPR, implicating pro-inflammatory T cells in the progression of ischemic neuronal injury. Finally, we made the remarkable observation that the novel CD4(+)CD40(+) (Th40) population of pro-inflammatory T cells that are strongly associated with autoimmunity are present in large numbers in the injured brain. These data indicate that studies investigating the neuro-immune response after global cerebral ischemia should consider the role of infiltrating T cells in orchestrating the acute and sustained immune response.